Refleksi Adab Murid terhadap Guru dalam Kitab Adab Al-Suluk Lil Murid: Relevansi terhadap Pendidikan Kontemporer - Hafiz, Muhammad; Mursal, Mursal (Instructional Development Journal, 2025)
This study deeply reflects upon the concept of student etiquette (adab) towards teachers as elucidated in Syekh Abdul Qadir al-Jilani's Kitab Adab al-Sulūk lil-Murīd, examining its relevance to contemporary education. Employing a qualitative approach with a library research method and hermeneutic content analysis, the study identifies fundamental principles of adab. Findings reveal that al-Jilani emphasizes sincere intention, profound reverence, obedience, humility, politeness in interaction, and a willingness to serve the teacher as core pillars. This adab is viewed not merely as etiquette but as a foundational prerequisite for the blessings of knowledge and spiritual success.  In the face of contemporary educational challenges, including moral degradation, the impact of digital disruption, and shifting values, these teachings prove critically relevant. The concept of sincerity balances pragmatic learning motivations, while reverence for teachers is crucial for restoring educators' authority among students. Obedience and patience foster resilience, and humility counteracts intellectual arrogance. Adapting these values is also pertinent to digital ethics. Integrating these classical adab principles is essential for creating a harmonious, effective learning environment and producing generations that are not only intellectually capable but also morally upright and virtuous. This research contributes to revitalizing character education by drawing upon Islamic local wisdom. TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//   This page is in Maltese Translate to Indonesian    AbkhazianAcehneseAcholiAfarAfrikaansAlbanianAlurAmharicArabicArmenianAssameseAvaricAwadhiAymaraAzerbaijaniBalineseBaluchiBambaraBaouléBashkirBasqueBatakBatak SimalungunBatak TobaBelarusianBembaBengaliBetawiBhojpuriBikolBosnianBretonBulgarianBuryatCantoneseCatalanCebuanoChamorroChechenChichewaChuukeseChuvashCorsicanCrimean TatarCrimean Tatar (Latin)CroatianCzechDanishDariDinkaDivehiDogriDombeDutchDyulaDzongkhaEnglishEnglish (USA)EsperantoEstonianEweFaroeseFijianFilipinoFinnishFonFrenchFrench (Canadian)FrisianFriulianFulahGaGalicianGeorgianGermanGreekGuaraniGujaratiHaitian CreoleHakha FalamHausaHawaiianHebrewHiligaynonHindiHmongHungarianHunsrikIbanIcelandicIgboIlocanoIndonesianInuktitutInuktitut (Latin)IrishItalianJamaican PatoisJapaneseJavaneseJingphoKalaallisutKannadaKanuriKapampanganKazakhKhasiKhmerKigaKikongoKinyarwandaKokborokKomiKonkani (Latin)KoreanKrioKurdish (Kurmanji)Kurdish (Sorani)KyrgyzLaoLatgalianLatinLatvianLigurianLimburgishLingalaLithuanianLombardLugandaLuoLuxembourgishMacedonianMadureseMaithiliMakassareseMalagasyMalayMalay (Arabic)MalayalamMalteseMamManxMaoriMarathiMariMarshalleseMarwariMauritian CreoleMeitei/Meetei (Mayek)MinangkabauMizoMongolianMyanmar (Burmese)N'Ko BambaraNahuatlNdau (Zimbabwe)NdebeleNepaliNewariNorthern SamiNorwegianNuerOccitanOdiaOromoOssetianPangasinanPapiamentoPashtoPersianPolishPortuguesePortuguese (Portugal)PunjabiPunjabi (Arabic)Q'eqchi'QuechuaRomaniRomanianRundiRussianSamoanSangoSanskritSantaliSantali (Latin)Scots GaelicSepediSerbianSesothoSeychellois CreoleShanShonaSicilianSilesianSimplified ChineseSindhiSinhalaSlovakSlovenianSomaliSpanishSundaneseSusuSwahiliSwatiSwedishTahitianTajikTamazightTamazight (Latin)TamilTatarTeluguTetumThaiTibetanTigrinyaTivTok PisinTonganTraditional ChineseTshilubaTsongaTswanaTuluTumbukaTurkishTurkmenTuvanTwiUdmurtUkrainianUrduUyghurUzbekVendaVenetianVietnameseWarayWelshWolofXhosaYakutYiddishYorubaYucatec MayaZapotecZulu Always translate Maltese to Indonesian Never translate Maltese Never translate ejournal.uin-suska.ac.id